Control interno de los procesos de recaudación y su incidencia en la gestión operativa del gobierno autónomo descentralizado municipal del cantón buena fe, periodo 2018 – 2019. - Arce Alcivar, Lorena Marilin (2020)
The purpose of this research is to determine the incidence of internal control of the collection processes in the operational management of the Municipal GAD of the Canton San Jacinto de Buena Fe 2018-2019. For which, an interview with the Head of Collections and a survey of the 10 members of the Collection Unit were used as research instruments, which allowed the identification of 2 collection processes that are: Collection for Payments at Treasury Windows and Collection through Collectors of Public Roads, where inconsistencies were detected such as the lack of personnel, especially for the collection of public highway taxes, lack of electronic devices to accept credit and debit card payments; and that the services of a security company that is in charge of transferring the collections are not available. Through the Internal Control Evaluation of the Collection Processes of the Municipal GAD of the San Jacinto de Buena Fe Canton, it was established that the level of confidence corresponding to the Years 2018 and 2019 is 63.72% and 66.92% respectively, which it is considered MODERATE. In addition, 9 operational management indicators were determined, which are: Staff Training, Efficiency in Customer Service, Infrastructure Works carried out, Project Formulation, Liquidity, Financial Solvency, Self-Sufficiency, Tax and Income Income, rates and contributions. Finally, it was determined that the independent variable has a 100% impact on the dependent variable according to the applied linear regression model and there is a PERFECT POSITIVE CORRELATION, which means that as the confidence level of the internal control of the processes increases collection will increase the level of operational management of the institution. Keywords: Internal control, Collection, Treasury, Operational Management